2015
DOI: 10.1016/j.jcmgh.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

IL33 Is a Stomach Alarmin That Initiates a Skewed Th2 Response to Injury and Infection

Abstract: Background & AimsInterleukin (IL)33 is a recently described alarmin that is highly expressed in the gastric mucosa and potently activates Th2 immunity. It may play a pivotal role during Helicobacter pylori infection. Here, we delineate the role of IL33 in the normal gastric mucosa and in response to gastropathy.MethodsIL33 expression was evaluated in mice and human biopsy specimens infected with H pylori and in mice after dosing with aspirin. IL33 expression was localized in the gastric mucosa using immunofluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
105
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(114 citation statements)
references
References 50 publications
9
105
0
Order By: Relevance
“…It is possible that factors and cytokines operating locally in the stomach also influence the expression of a Th2-dominant tissue response. For example, Buzzelli et al showed that IL-33 promoted a type 2 gastric inflammatory response in WT mice that resembles the AIG in DEREG mice (120). …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that factors and cytokines operating locally in the stomach also influence the expression of a Th2-dominant tissue response. For example, Buzzelli et al showed that IL-33 promoted a type 2 gastric inflammatory response in WT mice that resembles the AIG in DEREG mice (120). …”
Section: Discussionmentioning
confidence: 99%
“…Several additional cytokines are reported to be expressed in the inflamed gastric mucosa, including IL10, IL32, and IL33 43, 44, 45. Additional information is needed to understand how the complex milieu of cytokines that are present in an individual with chronic gastritis influences the risk of gastric cancer (Table 1).…”
Section: Human Studiesmentioning
confidence: 99%
“…The mechanism by which Helicobacter causes parietal cell loss is not known. The host inflammatory response, however, is thought to be critical both in human beings and in mouse models 3, 36, 63, 64, 65. In general, the immune response can be categorized along 2 distinct paradigms: innate and adaptive.…”
Section: Murine Models Of Gastric Preneoplasiamentioning
confidence: 99%
“…IL33 synergizes to promote a Th2 inflammatory response that activates innate and adaptive immune cells. IL33 generally is classified as an alarmin because of its release into the extracellular environment by necrotic or apoptotic cells 64 . IL33-treated mice develop SPEM and a robust inflammatory response in the lungs, intestine, and stomach, indicating that IL33 is sufficient to recruit inflammatory cells and drive mucous production within respiratory and gut epithelial tissue 64, 119.…”
Section: Murine Models Of Gastric Preneoplasiamentioning
confidence: 99%
See 1 more Smart Citation